Pemodelan SPK Persetujuan Ajuan Pinjaman Dengan Mengimplementasikan Metode Smart Dan Kriteria 7P - Listiyono, Hersatoto; Purwatiningtyas, P; Sunardi, S; Maskur, Ali; Supriyanto, Edi (STIKOM Tunas Bangsa Pematangsiantar, 2025)
This research aims to explore the utilization of a Decision Support System (DSS) in the loan application approval process using the SMART method. DSS helps identify, assess, and mitigate various types of risks associated with loans, enhancing the efficiency and productivity of loan processing operations. By automating repetitive tasks, streamlining workflows, and reducing manual intervention, it improves customer satisfaction by providing faster response times. DSS also helps lenders comply with applicable laws and regulations by incorporating compliance checks, regulatory guidelines, and audit trails into the loan processing workflow, thereby reducing the costs and risks associated with manual processes, errors, and inefficiencies in loan processing. Traditional loan assessment methods often require manual processes, leading to delays and inaccuracies. The SMART method (Specific, Measurable, Achievable, Relevant, Time-bound) offers a structured approach to implementing DSS with clear and measurable outcomes. By leveraging DSS, lenders can streamline the loan application process, enhance decision-making accuracy, and improve customer satisfaction. This study will investigate the use of a SMART-based DSS in the loan application workflow and provide insights into best practices for implementing a SMART-based DSS solution in lending institutions. The findings of this research will contribute to the optimization of loan application processes and the improvement of decision-making capabilities in the financial industry, consistently, objectively, and more quickly. The system has the capability to collect, store, and manage data related to loan applications.